Fused-fiber-photometry based on a low-autofluorescence wideband multimode circulator - Formozov, Andrey; Dieter, Alexander; Lamarre, Joseph; Laurence, Audrey; Boudoux, Caroline; Wiegert, Simon; Beaudette, Kathy (Optics express, 2024)
Analysis of fluorescent signals in biological samples is widely used in the fields of life science and medicine and can be achieved through conceptually distinct approaches. Here, we report the use of a wideband multimode circulator (WMC), a three-port optical fused-fiber device with an asymmetrical structure specifically designed to ensure efficient light transmission in both illumination and collection paths. It features a flat spectral response and is ideally suited for simultaneous excitation and detection of fluorescence in biological tissue. The WMC used in this work was further improved by minimizing its inherent background autofluorescence. Using the WMC, we demonstrate improved fluorescence detection against already existing fiber-based approaches. Finally, we utilize the WMC to establish fiber photometry recordings in vivo to infer neuronal activity in a small neuromodulatory nucleus in the brainstem of an awake mouse.
Online veröffentlicht: 26. November 2024
Gesehen am 08.04.2025